The Effect of Upper Eyelid Muller Muscle Conjunctival Resection Surgery on Lower Eyelid Position. (3rd July 2021) - Zloto, Ofira; Kapelushnik, Noa; Sharon, Tal; Prat, Daphna; Leshno, Ari; Ben Simon, Guy
ABSTRACT: Purpose : To examine whether Müller's-muscle-conjunctival-resection (MMCR) changes the position of the lower eyelid. Methods : Retrospective controlled-cohort study. All patients who underwent MMCR (study group) or blepharoplasty (control group) between January 2016 and September 2018 were recruited. The data retrieved from the patients' medical records included demographics, visual-acuity, eyelid parameters and dry-eye parameters before and 3 months after surgery. Frontal photographs of the patient's eyes in primary position were taken preoperatively and at 3 months postoperatively. The margin-reflex-distance 1 (MRD1) and MRD2 were evaluated. The preoperative and 3 months postoperative MRD1, MRD2, and dry-eye signs and symptoms were compared. Results : Sixty-nine patients underwent MMCR and 54 patients underwent blepharoplasty during the study period. There were significant changes in MRD2 after MMCR surgery compared to preoperative values ( P < .01, paired t-test), but no significant changes in MRD2 after blepharoplasty surgery ( P = .091, paired t-test). The mean changes in MRD2 (delta MRD2) were 0.51 in the MMCR group versus (−0.10) in the blepharoplasty group ( P = .04, t-test). Conclusions : The position of the lower eyelid was altered significantly in patients that underwent MMCR surgery. This sequela should be discussed with the patients before surgery and should be considered by physicians when planning ptosis surgery.